Analisis Beban Kerja Pada Produksi Beton Pracetak Untuk Menentukan Jumlah Kebutuhan Pekerja - Wahyu Rahman Dani; Jaka Purnama (Fakultas Teknik Universitas Tulang Bawang, 2024)
Manufacturing company PT. Varia Usaha Beton provides concrete products. On the concrete production line in Gresik, the company makes various types of concrete, one of which is precast concrete. In manufacturing activities, there are problems when carrying out production where there are orders whose production has not been fully realized. Aspects of workload can influence production demand which cannot be realized in its entirety because workers expend too much energy resulting in workers not being optimal and the limited number of workers resulting in demand not being met. To address this problem, researchers conducted a workload analysis on precast concrete production activities for each product and determined the number of workers needed according to production demand. The method used is using working time measurements and the Full Time Equivalent method to analyze workload and determine the number of workers according to the FTE value index. The results obtained after data processing and data calculations were carried out for operators working to produce precast concrete, 13 of which were overloaded and 2 of which were normal. After calculating the need for workers, the workers needed to meet the demand for precast concrete production requires 52 workers from the initial 24 workers. Keywords: Full-Time Equivalent, Workload, Worker Needs